STRATEGI MENINGKATKAN MOTIVASI BELAJAR SIWA GENERASI DIGITAL - Ahmad Fahroni (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2024)
Learning motivation has an important role in educational success, because it influences students' attitudes and behavior in the learning process. This research aims to identify strategies that can increase students' learning motivation, especially the digital generation, which has different characteristics compared to previous generations. This research uses a library research approach with data collection techniques through library research and documentation. The data collected was analyzed using the content analysis method. The research results show that the digital generation has characteristics such as high digital skills, pragmatic attitudes, and a desire to gain recognition. Learning motivation in the digital generation can be influenced by intrinsic and extrinsic factors, which can be strengthened by providing rewards, healthy competition, and the use of appropriate learning methods and media. This research contributes to the development of more effective learning strategies in increasing learning motivation in the digital era. It is hoped that these findings can help educators in designing more relevant approaches to facing challenges in education today.